(untitled) (Journal of Mechanical Engineering, 2013)
The experimental investigation of the performance of a combined solar ejector absorption coolingsystem has been carried out. The system was installed in the solar energy park at University KebangsaanMalaysia. The influence of various operating conditions on the COP is studied using evacuated tube solarcollectors and NH3-H2O as working fluid. The results showed that, the absorption chiller provides high COPthan that of the conventional absorption system. The maximum COP of the cycle in the order of 0.6 when theimprovements of rectifier and solution heat exchanger are added while the maximum increase in COP in case ofcombined cycle is about 50% higher than the basic cycle. This study is provided an actual compact unit of 1.5cooling capacity and operated under real outside conditions for Malaysia and similar tropical regions. DOI: http://dx.doi.org/10.3329/jme.v42i1.15978